A new HLA‐C*07 allele, C*07:02:70, identified in a Chinese individual. (21st July 2016) - Zhou, X.‐Y.; Jiang, P.; Cai, J.‐P.
Abstract : A novel allele HLA‐C*07:02:70 differs from HLA‐C*07:02:01:01 by a single nucleotide at position 987 (C>T).